Feminine readings in Valladolid de Michoacán, eighteenth century. The “library” of Ana Manuela Muñiz Sánchez de Tagle (Tzintzun, Revista de Estudios Históricos, 2016)
This article is part of a research related to the history of books and reading practicesin Mexico at the end of the viceroyalty. The trajectory of Ana Manuela MuñizSánchez de Tagle, the “library” that was able to form in the late eighteenth centuryand the analysis of its books, provide insight into the interests and literary tastes ofwomen from the New Spain and how they could access to reading materials, butat the same time, serves to stimulate a debate on the concept that had the peoplefrom the New Spain of their books collections and the sense historians have givennow. On the other hand, the study analyzes the mechanisms of formation of afeminine bookstore in a provincial town; the way it was organized by the owner,the spaces and practices of reading they used to use, the content of the books, aswell as the intellectual world they represented. The essay ends with the final yearsof Manuela Muniz.
Keywords: libraries; women; reading practices; Valladolid de Michoacán; eighteenth century